Factors Affecting Malaysia Tourists’ Destination Loyalty Behavior: A Case Study of Hatyai, Thailand - chutima wangbenmad (Management Institute Faculty of Economics Universitas Andalas, 2023)
Retaining the loyal visitors to revisit is highly crucial for generating the revenue in tourism destination as well as reducing the marketing expenses, this empirical study has been designed to primarily explore factors that motivate Malaysia tourists to revisit Hatyai and to identify the key factors that affect Malaysia Tourists Destination loyalty behavior. The results of this study indicated that “destination attractiveness” “social interaction” and “Cost/Price/Value” were the most important destination attributes and travel motives for malaysia tourists revisit to Hatyai. Concerning Malaysia tourists destination loyalty behavior, the result reveals that “destination attractiveness” “social interaction” and “price/value/cost” predicts Malaysia tourists’ destination loyalty behavior with R2 = 58.9%.